AgI‐Directed Triple‐Stranded Helicates with meta‐Ethynylpyridine Ligands. Issue 20 (3rd June 2014) - Li, Qiaolian; Huang, Fu; Fan, Yaxun; Wang, Yilin; Li, Jianfeng; He, Yujian; Jiang, Hua
Abstract: A series of triple‐stranded complexes, [1a 3 Ag]BF4, [1b 3 Ag]BF4, [2a 3 Ag2 ](BF4 )2, [2b 3 Ag2 ](BF4 )2, and [3 3 Ag3 ](BF4 )3, have been obtained through the self‐assembly of Ag I ions with p ‐phenylene ethynylpyridine ligands. X‐ray crystallographic studies unambiguously demonstrated a Ag I ‐directed monodentate triple‐stranded helical structure in the solid state for1b and2b . A combination of NMR spectroscopy, HRMS (ESI), and isothermal titration microcalorimetry studies further confirmed that strands1, 2, and3 are also able to form triple‐stranded helical structures in the presence of Ag I ions in solution. Abstract : A series of Ag I ‐directed monodentate triple‐stranded helicates have been prepared through the self‐assembly of Ag I ions with p ‐phenylene ethynylpyridine ligands.